FRAMING BERITA PENISTAAN AGAMA M. KECE DALAM PORTAL BERITA KOMPAS.COM EDISI AGUSTUS 2021 - Mukhlisa Setiabudi; Muliadi Mau; Tuti Bahfiarti (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2022)
Blasphemy cases are no longer a new case in a country with a pluralistic society like Indonesia. The blasphemy case by M. Kece is the latest case that has caught the public's attention. M. Kece is known to have committed acts of hate speech and insults to the Prophet Muhammad and Islam. This case then did not miss the attention of the media as Kompas.com also highlighted this case in absolutely a different way and construction. For this reason, this study discusses framing analysis with the Robert N. Entman model which consists of four points of analysis, namely defining of problem, diagnosing causes, making a moral judgment, and treatment recommendations on the Kompas.com news portal related to M. Kece's cause. This study uses a qualitative descriptive method with a constructionist approach to framing analysis. The results of this study concluded that Kompas.com tried to convey M. Kace's reporting accurately with subtle narrations so as not to tarnish the image of M. Kece because he was considered an ordinary YouTuber.